2013
DOI: 10.1167/iovs.12-10774
|View full text |Cite
|
Sign up to set email alerts
|

Wnt Signaling Promotes Müller Cell Proliferation and Survival after Injury

Abstract: PURPOSE.Müller glia respond to retinal injury by a reactive gliosis, but only rarely do mammalian glial cells re-enter the cell cycle and generate new neurons. In the nonmammalian retina, however, Müller glia act as stem/progenitor cells. Here, we tested the function of Wnt signaling in the postinjury retina, focusing on its ability to influence mammalian Müller cell dedifferentiation, proliferation, and neurogenesis. METHODS.A 532 nm frequency doubled neodymium-doped yttrium aluminum garnet (Nd:YAG) laser was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(59 citation statements)
references
References 76 publications
2
57
0
Order By: Relevance
“…In addition, HC regeneration might be related to HC degeneration in this study [21]. A similar relationship was observed in AC or GC regeneration after AC or GC loss in chickens [3,17,18] and rod cell regeneration after rod cell death in rodents [9][10][11]19,20]. These studies indicate that the types of damaged cells can provide a permissive or a stimulating environment for retinal regeneration of these cell types.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…In addition, HC regeneration might be related to HC degeneration in this study [21]. A similar relationship was observed in AC or GC regeneration after AC or GC loss in chickens [3,17,18] and rod cell regeneration after rod cell death in rodents [9][10][11]19,20]. These studies indicate that the types of damaged cells can provide a permissive or a stimulating environment for retinal regeneration of these cell types.…”
Section: Discussionsupporting
confidence: 81%
“…Several experiments have proven that damage to the mammalian retina drives MGCs to re-enter the cell cycle, and some of the cells subsequently differentiate into cells expressing neuronal markers [4,[7][8][9][10][11]19]. In these studies, the number of BrdU + MGCs remains at a low level and as a result, the number of new neurons is even lower.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3a). In contrast to corneal studies, the role of WNT signaling in the posterior pole has been examined in various parts of the tissue, such as the neural retina, retinal vasculature and retinal pigment epithelium [24][25][26][27][28] . To evaluate the expression pattern of WNT7B in the posterior pole of eyes, we examined the localization of WNT7B in the mouse eye.…”
Section: Resultsmentioning
confidence: 99%
“…They express the same neurogenic genes, such as Notch and Wnt, as those found in the fish 17,18 , and can be reprogrammed in a dish to become retinal neural or photoreceptor progenitors 19,20 . In vivo, it has been shown that, by targeting specific signaling pathways through administering fibroblast growth factor (FGF) 21 , Notch 22,23 , Wnt [24][25][26] , or sonic hedgehog 27 , a significant number of Müller cells can be induced to re-enter the cell cycle and display properties of retinal progenitors. While transcription factor Ascl1a was shown to be required for retinal regeneration in the fish 12,14,28 , recent report indicates that overexpressing a single transcription factor, Ascl1, is also sufficient to induce a neurogenic state of mature Müller cells of mice 29 .…”
Section: Sources Of Endogenous Stem Cells/progenitor Cellsmentioning
confidence: 99%